A secure social networking application for primary school kids in Malaysia: KIGGLES! / Raja Noor Diyana Raja Ezar Ishamuddin ... [et al.] - Raja Ezar Ishamuddin, Raja Noor Diyana; Ahamad Sabri, Salihah; Nadia Sulaiman, Syahira; Wan Azuan, Wan Anis Natasha; Iberahim, Hadijah (2021)
This study investigates parents, guardians, and teachers' perceptions of the gadget utilization for social networking among their kids, particularly the primary school children during the Covid-19. The study conducted a comparative analysis on available social networking applications to determine the safety and risk level. Interviews feedback imply that an adequately designed social networking application for young users and serves the concerns of the parents, guardian, and teacher on the safety of children, socially, physically, and mentally, is needed. The results proposed some features to be given attention in attracting the children into learning and engagement. This study outlines the elements of a secure social networking application user-friendly to the kids and parents, the 'KIGGLES!'. The features of a colourful layout and fun learning activities will benefit the children. The novelty of the application is mainly three; 1) limits in accessibility time, 2) safety and privacy screening, and 3) tracing, tracking, and monitoring system for parents on children access and progress. It is the potential to be commercialized with extended features that align with Malaysia Education Blueprint.